S103 No Loss In Efficacy Following Switch From Salmeterol/fluticasone Combination To Indacaterol Monotherapy In Patients With Moderate Copd: The Instead Study. (10th November 2014) - Rossi, Andrea; Molen, Thys van der; Olmo, Ricardo Del; Papi, Alberto; Webhe, Luis; Quinn, Matthew; Lu, Chengxing; Young, David; Cameron, Ray; Bucchioni, Enrica; Altman, Pablo
Abstract : Introduction: Many patients with low risk of COPD exacerbations receive twice-daily ( bid ) LABA/ICS, salmeterol/fluticasone (SFC), for maintenance treatment. This study evaluated the effect of switching these patients to a once-daily ( od ) LABA, indacaterol, monotherapy. Methods: INSTEAD was a 26-week double-blind, double-dummy study in patients aged ≥40 years, with moderate COPD (post-bronchodilator FEV1 50–80% predicted) and no exacerbations in the past 12 months, who were receiving SFC 50/500 μg bid for ≥3 months prior to study entry. Patients were randomised (1:1) to continue with SFC 50/500 μg or to be switched (with no washout) to indacaterol 150 μg. The primary objective was to demonstrate non-inferiority of indacaterol to SFC, measured by trough FEV1 after 12 weeks (non-inferiority margin: 60 mL). Trough FEV1 was also evaluated at 4, 8 and 26 weeks. TDI and SGRQ-C total scores were evaluated at Weeks 12 and 26; the annualised rate of exacerbations and safety were evaluated over 26 weeks. Results: A total of581 patients were randomised (indacaterol: 293; SFC: 288); 85.4% completed the study. The primary endpoint was met, with a LSM difference in trough FEV1 between indacaterol and SFC of –9 mL (95% CI: –45 to 26 mL; p = 0·002 for NI). There were no significant differences between treatments in trough FEV1 at any of the other visits (Baseline and Weeks 4, 8 and 26). The TDI and SGRQ-C total scores and their responder rates were similar between two treatments, at both Weeks 12 and 26 (Table 1 ). During the 26 week treatment period, 79.5% and 74.7% of patients in the indacaterol and SFC groups, respectively, experienced no exacerbations. There was no statistically significant difference between treatments in the rate of all COPD exacerbations per year, with rates of 0.57 vs 0.67, respectively (RR 0.86 [95% CI 0.62, 1.20]; p = 0.367). Adverse events (AEs) and serious AEs were comparable between the treatment arms. Conclusion: Indacaterol was non-inferior to SFC in terms of bronchodilation and showed similar efficacy in terms of breathlessness, health status, and exacerbation rate indicating that this group of patients can be switched from SFC to indacaterol 150 µg with no loss in efficacy.